The use of ultrasound measurement system to monitor the mechanical integrity of rolling element bearings and gears - Tu, X. (Cranfield University, 1992)
A theoretical design and study of production of various types of ultrasound transducers for acoustic emission research into the fatigue failure mechanism and application in machine condition monitoring of rolling element bearings and gears are reported. The transducer transmission modelling was presented and verified, theoretical transducer responses were exercised and their comparisons were made with experimental results. Transducer size, construction and location were considered important in the application of ultrasound. Advanced method of metallurgical attachment improved the bond durability and reliability, the signal transmission as well as the capability of withstanding a hostile environment (117 °C) within the vicinity of the component being monitored. In-Situ calibration provided a means of ensuring the in- service transducer performance and the sensing circuitry as a whole. _ The smallest fabricated transducer had a circular sensor of 2.6 mm diameter and 0.5 mm thick, which was highly sensitive to a few milli-meter stress wavelength. The ring type transducer was preliminarily found to improve the amplication range. r Five rolling element bearings were tested using the purposely designed ultrasound transducers, the experimental observations of the detected signal were then time- amplitude distribution displayed. The changing stages of failure development from a single fatigue spall of less than 3 mm to 1.5 mm in length and down to surface crackings of 25 m long, were appropriately explained. Two pairs of test gears having three different fault conditions (good, moderate and severe) were conducted on a Roll-Royce back-to-back gearbox test rig at 1000 RPM to 2000 RPM approximately. Transducers implanted inside the gearbox sensitively showed the gradual changes in amplitude distribution resulting from the fault incremental category. A study of signal transmission of the fault in a gear assembly revealed that half of the elastic stress wave energy was lost by the time it arrived at the support bearing. Statistical methods using RMS and kurtosis parameter a fault indicator were employed to evaluate the bearing and gearbox data. High frequency analysis confirmed that failed bearing or gear signatures were ultrasonic, in addition the signal frequencies below 50 kHz were also detectable by the purposely designed transducers. A defect simulation was also established to study the gearbox failure, its usefulness was then discussed.